EURASIP Journal on Image and Video Processing - Dugelay, Jean-Luc.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
EURASIP Journal on Image and Video Processing is intended for researchers from both academia and industry, who are active in the multidisciplinary field of image and video processing. The scope of the journal covers all theoretical and practical aspects of the domain, from basic research to development of application. Contributed articles on image and video processing may be focused on specific techniques (e.g., wavelets, mathematical morphology, Markov models), diverse functionalities and services (e.g., classification, compression, identification, protection, recognition, restoration and segmentation), within the context of various activity sectors (e.g., multimedia, medical, aerial, robotics, security, communications, arts) employing diverse data formats (e.g., black and white, gray scale, color, multi spectral, infra red, video, stereo, 3-D). The journal is an Open Access journal since 2007.
Keywords: Image processing; Pattern recognition; Biometrics (Biology).; Signal processing; Speech processing systems; Signal,Image and Speech Processing; Image Processing and Computer Vision; Biometrics; Pattern Recognition